2018
DOI: 10.1038/nm.4506
|View full text |Cite
|
Sign up to set email alerts
|

Genital inflammation undermines the effectiveness of tenofovir gel in preventing HIV acquisition in women

Abstract: Several clinical trials have demonstrated that antiretroviral (ARV) drugs, taken as pre-exposure prophylaxis (PrEP), can prevent HIV infection1, with the magnitude of protection ranging from -49 to 86%2–11. While these divergent outcomes are thought to be due primarily to product adherence12, biological factors likely contribute13. Despite selective recruitment of higher risk participants for prevention trials, HIV risk is heterogeneous, even within higher risk groups14–16. To determine whether this heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 38 publications
1
110
0
2
Order By: Relevance
“…There may also be beneficial effects of using PrEP along with an anti-inflammatory drug. A recent study from McKinnon et al showed that genital inflammation among African women using anti-HIV drug tenofovir in a vaginal gel reduced the effectiveness of the HIV prevention approach from 57% to 3% [22]. If vaginal inflammation can be reduced it may actually aid other prevention approaches.…”
Section: Discussionmentioning
confidence: 99%
“…There may also be beneficial effects of using PrEP along with an anti-inflammatory drug. A recent study from McKinnon et al showed that genital inflammation among African women using anti-HIV drug tenofovir in a vaginal gel reduced the effectiveness of the HIV prevention approach from 57% to 3% [22]. If vaginal inflammation can be reduced it may actually aid other prevention approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Raised pre‐infection genital concentrations of inflammatory cytokines (macrophage inflammatory protein (MIP)‐1α and MIP‐1β) were present in women who acquired HIV infection compared to women who remained uninfected . These inflammatory changes were associated with elevated levels of highly activated T cells in the genital mucosa and decreased efficacy of the antiretroviral drug tenofovir, which is a reverse transcriptase inhibitor that was assessed for its effectiveness in preventing HIV infections . In rhesus macaques, the establishment of a productive simian immunodeficiency virus (SIV) infection in the genital mucosa required local chemokines, which facilitated recruitment of CD4+ T cells to the site of infection, and enabled SIV expansion and establishment of infection .…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria possess a variety of enzymatic mechanisms for drug metabolism, including hydrolases, oxidoreductases, lyases, and transferases with established impact on dozens of licensed drugs . Genital inflammation, defined by the presence of pro‐inflammatory cytokines in CVL, was associated with no protective benefit of TFV gel in the CAPRISA 004 study compared to a 75% relative risk reduction in women without genital inflammation . These findings indicate a need for prospective assessment of microbial metabolism of PrEP drug candidates, reassessment of drug concentration‐based adherence measures in trials of topical drugs, and consideration of inflammation as an explanatory variable in future clinical trials.…”
Section: Understanding Heterogeneous Prep Outcomesmentioning
confidence: 99%